Lutzomyia (Diptera: Psychodidae) in the collection of the Universidad del Valle, Facultad de Salud, Cali - BARRETO, MAURICIO; BURBANO, MARÍA ELENA; BARRETO, PABLO (Revista Colombiana de Entomología, 2010)
The Collection of Arthropods of Medical Importance of the Universidad del Valle, Facultad de Salud holds 14,877 specimens of Lutzomyia from Colombia, which corresponds to 76 species and subspecies. A list of these species is presented with the number of females, males, and Colombian departments (states) of origin. In addition, 12 morespecies from eight other countries are indicated as represented in the Collection. The value of this material, which includes type specimens, is discussed, as well as the importance of preserving samples in biological collections.